Application of the Adaptive Cycle and Panarchy in La Marjaleria Social-Ecological System: Reflections for Operability - Marc Escamilla Nacher; Carla Sofia Santos Ferreira; Michael Jones; Zahra Kalantari (Land, 2021)
The adaptive cycle and panarchy are recognised tools for resilience assessment prior to establishing new management approaches aligned with Anthropocene needs. This study used the adaptive cycle and panarchy to assess the dynamics of the social-ecological system (SES) of La Marjaleria, Spain, which experienced increasing human pressure and environmental degradation in recent decades, and developed the ‘adaptive curve’ as a novel graphical representation of system change in the presentation of the results. Based on a literature review of historical changes in La Marjaleria, a SES analysis was performed using the adaptive cycle and panarchy, following the Resilience Alliance’s Practitioners Guide. The assessment offered new insights into the social and ecological dynamics of La Marjaleria through identification of causes and consequences from a complex systems perspective. Previous land-use management in the area has generated tensions between different stakeholders and reduced environmental resilience. The systems thinking approach highlighted the complexity of change processes, offering the possibility of new routes for dialogue and understanding. The ‘adaptive curve’ developed as a method of illustrating interactions across scales in this study could be useful for synthesising the results of a panarchy analysis and supporting their interpretation, offering relevant departure points for future planning and decision-making.